Waveguide-based TIRFM for Diagnostic Applications - ALIZADEHHEIDARI, MOHAMMADREZA (My University, 2012)
The ultimate need for disease diagnostics necessitate the recognition of low abundant diseasespecific biomarkers and also specific biomolecules interaction from millions of interaction occurring in every single cell in the human body. With this aim many novel diagnostic techniques have been developed in the past decades, but further improvements in detection sensitivity in the fM-aM analyte concentration are required. Fluorescence microscopy is one the most commonly used techniques in the life-sciences today. It is based on the excitation of fluorophore markers labeled to molecules of interest and the collection of fluorescently emitted light with microscope objective. Of the several fluorescence microscopy techniques developed so far, total internal reflection fluorescence microscopy (TIRFM) is one of the most frequently used technique for studying biological interactions at or close to interfaces. The aim of this study is to design a simple, small and cheap waveguide-based TIRFM setup which is comparable to conventional TIRMF systems to be used in clinical environment in diagnostic applications.
Keywords: Fysik; Biologiska vetenskaper; Physical Sciences; Biological Sciences